Introduction to engineering design and problem solving (McGraw-Hill, 2002)
Many freshman, introductory engineering courses have increasingly moved to a cluster of individual, topical books to communicate the engineering fundamentals each individual college or university finds most appropriate for their students. McGraw-Hill's modular answer is the BEST series. For those instructors who want the flavor of Eide's fundamentals approach based on his longer, hard cover textbook, but desire a shorter text to complement other application specific texts, McGraw-Hill offers this BEST version -- Eide's Introduction to Engineering Problem Solving and Design, 2nd edition. In previous years, Eide has had two BEST books, one for problem solving and one for design. The two best books have been combined in this BEST book, Introduction to Engineering Problem Solving and Design, 2nd edition. If instructors are interested in using material from this BEST book along with material from other BEST books, use PRIMIS to build a customized book. Visit www.mhhe.com/primis/online. Customized books may be sold traditionally through college bookstores or electronically through McGraw-Hill's eBookstore. In this new edition the author has updated the treatment of the two most important topics treated in introductory engineering courses -- problem solving and design. The contents are directly derived from the author's 4th edition revision of his hard cover book, Engineering Fundamentals and Problem Solving. The design material in particular is expanded and has more diverse examples as well as even more projects.